Perceived sources of stress among postgraduate students of a dental college in Karnataka, India - M J Mathew; C B Sudeep; Jithesh Jain; Vipin Jain (Wolters Kluwer Medknow Publications, 2017)
Introduction: Dentistry has for some time been viewed as a profession with high-stress, and usually this begins from the days of dental school onward. Students are subjected to different kinds of stressors, some being the pressure from academics with an obligation to succeed, uncertainty regarding their future and difficulties of integrating into the system. Aim: The aim is to identify the perceived sources of stress among postgraduate students from a dental college in Coorg, Karnataka. Materials and Methods: A cross-sectional questionnaire study was carried out, and the study samples included all the postgraduates of all nine specialties, including all the seventy-seven postgraduate students as samples. Results: Stress was relatively general among all the groups of the study participants, certain factors or stressors such as the amount of assigned work, competition with peers, examination and grades, lack of confidence to be a successful student and fear of facing parents after failure hamper the academic life of these students and had more significance among groups when compared to others. Conclusion: The academic life of students seemed to be hampered due to various potential stressors such as the amount of assigned work, competition with peers, examination and grades, lack of confidence to be a successful student, and fear of facing parents after failure. Such issues that arise in the educational setting need to be addressed which will help improve the academic environment of the students.